Managing cultural diversity for collective identity: A case study of an ELT department in Omani higher education. (November 2021) - Al Muqarshi, Amal; Kaparou, Maria; Kelly, Anthony
This paper employs a social identity approach to explore the management of a collective organizational culture in a culturally diverse context. Literature suggests that cultural diversity can be an asset for organizations if managed effectively. This study employs a qualitative case-study design, drawn on data generated for a larger project that utilized 16 interviews, eight team meetings' observations, document analysis and field notes. It instrumentally uses a Department of English as its site due to the prevalence of cultural diversity in such context. The paper explores whether leadership is perceived as effective towards establishing a collective identity in an Omani higher education (HE) domain. The findings suggest that leadership impact is restricted by the central management of the system that translates largely into transactional leadership and hierarchical approaches at the level of the group and largely fails to establish such an inclusive identity. The paper argues that in a globalizing era, Omani HE can only view cultural diversity as an asset that aids its intellectual capital establishment. Hence, it should cater for such a composition and engineer it effectively to achieve better alignment with the requirements of the current market. These findings can be of value to policy makers, researchers and professionals in HE.